Giftedness Analysis Using Sport Search on Physical Education Learning for Elementary School Students in Surakarta City - Matsuri Matsuri; Idam Ragil Widianto Atmojo; Tri Budiharto; Dwi Yuniasih Saputri; Sularmi Sularmi; Roy Ardiansyah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to analyze the talents/giftedness possessed by elementary school students in Surakarta in 2022. The research used a descriptive method, with a survey technique of talent scouting of sports search model utilizing sports search software. The sample of this study amounted to 50 students, who were taken using the total sampling technique. The research instrument employed a talent scouting test of the sport search model. After the data were obtained, they were analyzed narratively to provide a more explicit meaning using the interactive analysis model by Miles and Huberman. The results revealed that 35 students (35%) had potential giftedness, 31 students (31%) were less talented, and 34 students (34%) were not gifted. Research suggestions are to train seriously for students with talent, to keep training by adding training for less gifted ones, and to keep training seriously by increasing speed, agility, and endurance training for those who are not gifted. In addition, the identification results of students with potential in sports are needed so that later, these students will succeed in the right training process and can accomplish high achievements to support the development and improvement of sports success in Surakarta City.